Vulnerable and Forgotten: The Impact of the COVID-19 Pandemic on Autism Special Schools in England - Crane, Laura; Adu, Freddie; Arocas, Francesca; Carli, Rachel; Eccles, Simon; Harris, Stewart; Jardine, Jayne; Phillips, Chloe; Piper, Sue; Santi, Lucia; Sartin, Matthew; Shepherd, Claire; et al. (Frontiers in Education, 2021)
The COVID-19 pandemic has caused, and continues to cause, unprecedented disruption in England. The impact of the pandemic on the English education system has been significant, especially for children and young people with special educational needs and disabilities (SEND). While it was encouraging that the educational rights of children and young people with SEND were highlighted during the COVID-19 pandemic, Government decision-making appeared to be centered around the needs of pupils in mainstream schools. In this article, co-authored by an academic researcher and senior leaders from the Pan London Autism Schools Network (PLASN; a collective of special schools in London and the South East of England, catering for pupils on the autistic spectrum), we reflect on the impact of the COVID-19 pandemic on special schools in England. We document and discuss a range of challenges experienced by PLASN schools, including the educational inequalities that were exposed and perpetuated by the COVID-19 pandemic, as well as the manner in which the needs and realities of special schools were overlooked by the Government. We also detail the creative and innovative solutions implemented by PLASN schools to overcome barriers that they encountered. These solutions centered on facilitating holistic approaches to support, ensuring clear and regular communication with families, providing effective support for home learning, and promoting collaborative ways of working; all of which align with good practice principles in autism education more generally, and are essential elements of practice to maintain post-pandemic. We additionally reflect on how the COVID-19 pandemic could be a catalyst for much-needed change to the SEND system: leading to better educational provision, and therefore better outcomes, for pupils with SEND.